Computers, Time and Speed: Five Slow Tech Case Studies - Whitehouse, Diane; Patrignani, Norberto (CCSD, 2014)
Part 1: Society, Social Responsibility, Ethics and ICT International audience This chapter examines briefly the notions of time and speed. It introduces the notion of Slow Tech: information technology that is good, clean and fair, and places an especial emphasis on technology that is clean. This chapter does not delve deep into the Slow Tech concept. Rather, it highlights a set of arguments about why speed is not always important or necessary. People are now increasingly beginning to think about much longer periods and phases that may extend at least as long as the existence of human beings on the globe. As illustrations, the chapter explores five specific case studies. Each comes from a different location, yet all describe global implications and challenges. One example is in fact a mathematical model. Two sites, in sympathy with the location of the Human Choice and Computing 11 (HCC11) conference, are from Scandinavia – one from Onkalo, Finland, and a second from Svalbard, a northern Norwegian island. A further two cases are from the United States of America. The logic behind these five case studies strengthens the arguments about why − with the support of the Slow Tech concept − it is increasingly important for society and its many stakeholders to question the current information and communication technology (ICT) obsession with speed and rethink the relationships between society and technology.